Students' Perceptions in Learning English Online for Developing Listening Skills in Grade 7 Madrasah Tsanawiyah: Persepsi Siswa Dalam Pembelajaran Bahasa Inggris Online Untuk Pengembangan Keterampilan Mendengar Di Kelas 7 Madrasah Tsanawiyah - Lisa Gryta Fabiola; Wahyu Taufiq (Academia Open, 2021)
This research aims to find out Students’ Perceptions Of English Online Learning For Listening Skill Development In 7th Grade Of MTSN 1 Sidoarjo. In this study, the researcher used a descriptive-quantitative research design. This research involved 32 students of VII-A class in MTSN 1 Sidoarjo. The data collection was taken from a questionnaire adapted from Al-Khatiri and Arnold Lund. The highest average comes from statement number 3 with an average of 3.8. The result of this study indicates that students’ perception Of English Online Learning For Listening Skill Development In 7th Grade has a positive perception. This method helps the students to be more productive in terms of understanding English learning material while this method saves their efforts and time to submit the assignment online.